Stance-taking and identity construction in supervisor-supervisee interaction / Rami Maher Delli - Delli, Rami Maher (2014)
Interactions between supervisor and supervisee during consultation particularly in the postgraduate level are essential in the completion of a thesis or dissertation. In most interactions, both speakers; the supervisor and the supervisee assert their identities who they are. Such scenario has been an important phenomenon to examine how stance-taking and identity construction are portrayed. This research specifically examined 10 conversations between supervisors and supervisees during research consultations at the University of Malaya, Kuala Lumpur, Malaysia. The study combined the Stance Triangle and Model of Stance Marker as theoretical framework in analyzing the construction of identity between supervisors and supervisees. In addition, conversation analysis was used as an approach in analyzing the data. The findings of the study show that in supervisor-supervisee interaction certain stages are followed in the conversational structure. This study reveals that there are 6 stages in supervisor-supervisee interaction, such as, making follow-up, testing the knowledge of the supervisee, giving suggestion, seeking for clarification, giving recommendation and making conclusion. In every stage, it shows that different stance takings are used by both supervisors and supervisees. Furthermore, the study reveals that epistemic stance markers, textual stance markers, attitudinal stance markers and deontic stance markers are commonly used. In every stance that supervisors and supervisees take, they tend to position their identities. Such identities shift from one stage to another. Generally, the supervisors position themselves as mentor, expert, counselor, knowledgeable, controlling and responsible. On the other hand, supervisees position themselves as mentee, neophyte, counselee, learner, follower and grateful.